Family Governance and the Moral Obligation of Businesses to Serve Their Communities - R, Steffi.; Rajest, S. Suman; Regin, R.; T, Shynu (Research Parks Publishing LLC, 2023)
The concept of corporate social responsibility is increasingly being embraced by businesses of all kinds and in all areas of society. The necessity of conducting an investigation on the level of Corporate Social Responsibility performance by family businesses is one of the aims of this article. Second, the purpose of this article was to investigate how well non-family businesses perform in terms of their corporate social responsibility obligations. The practise of corporate social responsibility has continued to gain ground in the business world. In the context of a company,